Document-Oriented NoSQL Databases Performance Analysis of MongoDB and MySQL using PHP - Hazim, Dhulfiqar (My University, 2014)
Huge amounts of data that is increasing day by day cannot be managed easily by relational databases because of low scalability provided by these databases. The storage technology is still not capable enough for the performance and scalability that is needed, after 2005 NoSQL databases have come and start solving the problems that relational databases was facing before. NoSQL is a type of database that under non - relational databases. There are four types of NoSQL databases, these types are (Key Value Store – Column Store – Document databases – Graph databases) each one of these databases has different presenting, advantage, disadvantage, and features. Non - relational databases giving a significant change of how enterprise applications built. The q uestions of whether non - relational databases are the right choice or stay with the old relational databases for applications and web development, from where NoSQL came from, how they are represented , and what are the types of relational and non - relational databases, these questions are going to be explained in this thesis. The objectives of this thesis are to show that the need of NoSQL databases became necessary with the time, second objective is to show the types and representation of relational and non - relational databases, third objective is to focus about MongoDB that is a type of Document Databases under the category of NoSQL database that is a non - relational database. Illustrating an example of Hospital Management System (HMS) which is developed in P HP and uses MongoDB as the database and the last point is comparing MySQL that is a relational database with MongoDB by how to represent these two databases and how to write answers for same query in MySQL and MongoDB, then a comparison analysis by calcula ting the time of selection, insertion, updating and deleting between MongoDB and MySQL with the help of PHP.
Master of Engineering-Dissertation
Keywords: NOSQL database; mongoDB; document-oriented databases; MySQL